Horn, or the counterside of media - Schmidgen, Henning (Sign, storage, transmission., 2022)
"Henning Schmidgen reflects on the dynamic phenomena of touch in media, analyzing works by artists, scientists, and philosophers ranging from Salvador Dalí to Walter Benjamin, who each explore the interplay between tactility and technological and biological surfaces."--